"I'm a monster, but I'm not a monster": symbolic and social identity work among child sexual exploitation material users - Rimer, Jonah R. (International criminal justice review, 2024)
Child sexual exploitation material (CSEM) users elicit strong negative reactions from society and people within their networks. There are symbolic and social boundaries that these individuals have transgressed, and subsequent identity work involves the negotiation of self and self-presentation. This article combines results from two studies to explore negotiation of identity, symbolic and social boundaries, and associated narratives among 103 CSEM users. One study was an anthropological ethnography with 17 months of UK fieldwork in community-based group programs, and the other involved four months of interviews in sexual offense treatment units of a US prison. Participants’ identity work had commonalities: distinguishing between acts vs identities; differentiating crimes from identities; comparing offenses to others viewed as worse; framing childhood experiences as influencing offending; and situating both offending and post-offending identities within larger society. Results are discussed in the context of debates about risk, treatment, prevention, harm, denial/downplay/minimization, and reintegration. Furthermore, we highlight how identity work occurs within potentially competing/contrasting personal, judicial, treatment, media, and societal reactions to and expectations of individuals who have committed sexual offenses. Finally, we demonstrate the methodological and analytical value of cross-disciplinary comparative qualitative research by showing similarities across participants from different countries, settings, timeframes, and interventions.